Islam di era negara-bangsa. Politik dan kebangkitan agama muslim Asia Tenggara - HEFNER, Robert W. (Tiara Wacana Yogyakarta, 2001)
Islam di era negara-bangsa. Politik dan kebangkitan agama muslim Asia Tenggara